Anemia in HIV-Infected Children on ART in Uganda: High Risk Associations with Malaria, Opportunistic Infections, and Poor Adherence - Christopher Lyatinga Anyelwisye; Jimmy Kata Ogwal; Simon Evarist Kadogosa; Rauben Timuzigu; Cricent Anyetaba; Robert Wagubi; Clinton Olong; Elizabeth A John; Enoch Muwanguzi; Benson Okongo (HIV/AIDS-Research and Palliative Care, 2026)
Purpose: This study aimed to determine the prevalence and associated factors of anemia among HIV-positive children receiving antiretroviral therapy (ART) at two urban clinics in Mbarara City, Southwestern Uganda. Patients and Methods: We conducted a cross-sectional study among 293 HIV-positive children (<18 years) attending ART clinics at Mbarara Municipal Health Center IV and Holy Innocent Children’s Hospital between July and September 2025. A structured questionnaire captured sociodemographic and clinical data. Venous blood were collected for complete blood count (CBC) analysis, and stool samples were examined for intestinal parasites. Data on CD4 count and viral load were abstracted from medical records. Anemia was defined using age-specific WHO criteria. Bivariate and multivariate logistic regression analyses were performed to identify factors associated with anemia, with statistical significance set at p ≤ 0.05. Results: The overall prevalence of anemia was 6.14% (95% CI: 3.4% – 8.9%). Normocytic normochromic anemia was the predominant morphological type (72.2%). In the multivariate analysis, a recent episode of malaria (AOR = 9.61; 95% CI: 3.26–28.34), the presence of an opportunistic infection (AOR = 6.78; 95% CI: 1.28–35.83), and poor adherence to ART (AOR = 14.75; 95% CI: 1.31–165.65) were independently and significantly correlated with anaemia. Conclusion: While the prevalence of anemia in this cohort of HIV-infected children on ART was lower than global averages, it remains a significant clinical concern. The strong associations with malaria, opportunistic infections, and suboptimal ART adherence highlight critical areas for intervention. Targeted strategies, including integrated malaria control, enhanced prevention and management of OIs, and reinforced adherence support, are required to decrease the anaemia burden and optimize health outcomes in this at-risk population.
Keywords: anemia; HIV; children; antiretroviral therapy; ART; Uganda